Dopamine synthesis capacity correlates with µ-opioid receptor availability in the human basal ganglia: A triple-tracer PET study - Joonas Majuri; Juho Joutsa; Eveliina Arponen; Sarita Forsback; Valtteri Kaasinen (Academic Press Inc., 2022)
Animal studies have suggested that dopamine and opioid neurotransmitter systems interact in brain regions that are relevant for reward functions, but data in humans are very limited. The interaction is potentially important in disorders affecting these neurotransmitter systems, such as addiction. Here, we investigated whether subcortical μ-opioid receptor (MOR) availability and presynaptic dopamine synthesis capacity are correlated in the healthy human brain or in pathological gamblers (PGs) using positron emission tomography with 6-[18F]fluoro-l-dopa and [11C]carfentanil. The specificity of the findings was further investigated by including a serotonin transporter ligand, [11C]MADAM, as a negative control. Thirteen PG patients and 15 age-, sex- and weight-matched controls underwent the scans. In both groups, presynaptic dopamine synthesis capacity was associated with MOR availability in the putamen, caudate nucleus and globus pallidus. No similar associations were observed between dopamine synthesis capacity and [11C]MADAM binding, supporting a specific interplay between presynaptic dopamine neurotransmission and opioid receptor function in the basal ganglia. Correlations were similar between the groups, suggesting that the dopamine-opioid link is general and unaffected by behavioral addiction. The results provide in vivo human evidence of a connection between endogenous opioid and dopamine signaling in the brain.